(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In recent years, sustainability has become one of the key dimensions of business performance. The sustainability must be effectively communicated in suitable reports, the quality of which is determined by several factors. The paper aims to analyse the various dimensions of sustainability and relate them with the variables of corporate governance and sustainable development goals (SDG). This study supports policymakers and practitioners as it measures the breadth of sustainability information.